1985
DOI: 10.1152/jappl.1985.58.5.1438
|View full text |Cite
|
Sign up to set email alerts
|

Action of abdominal muscles on rib cage in humans

Abstract: To assess the actions of the rectus abdominis and external oblique muscles on the rib cage in humans, these two muscles were stimulated with surface electrodes in four normal supine subjects at functional residual capacity. Changes in anteroposterior and transverse rib cage diameters and changes in xiphipubic distance were measured with pairs of magnetometers. Stimulation of rectus abdominis produced a marked decrease in the xiphipubic distance and in the anteroposterior diameter, thus making the rib cage more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0
2

Year Published

1992
1992
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(41 citation statements)
references
References 0 publications
2
37
0
2
Order By: Relevance
“…It has been demonstrated that isolated stimulation of the rectus abdominis in healthy humans produces a marked caudal displacement of the sternum and a large decrease in the rib cage anteroposterior diameter. 18,19 Our results con®rm such action in tetraplegic patients. RT measurements were greater when the patient's voluntary e ort was combined with ES of abdominal muscles than when it was not.…”
Section: Discussionsupporting
confidence: 66%
“…It has been demonstrated that isolated stimulation of the rectus abdominis in healthy humans produces a marked caudal displacement of the sternum and a large decrease in the rib cage anteroposterior diameter. 18,19 Our results con®rm such action in tetraplegic patients. RT measurements were greater when the patient's voluntary e ort was combined with ES of abdominal muscles than when it was not.…”
Section: Discussionsupporting
confidence: 66%
“…Indirectly these muscles by increasing intra abdominal pressure cause passive distension of the diaphragm which by acting over its zone of apposition to the lower rib cage expands this part of the rib cage (Mier et al, 1985). The RA and EO each act differently on the rib cage.…”
Section: Role Of Abdominal Muscles In Respirationmentioning
confidence: 99%
“…When activated together, the distortion of the rib cage will depend on the relative strength of contraction of each of the muscles. The IO and TA were not tested (Mier et al, 1985).…”
Section: Role Of Abdominal Muscles In Respirationmentioning
confidence: 99%
“…These include the rectus abdominis (RA), external oblique (EO), internal oblique (IO), and transverse abdominis muscles (TrA). The action of the RA produces a caudal displacement of the sternum, and a decrease in the anteroposterior diameter of the rib cage (4). Contraction of the EO causes a caudal displacement and a decrease in the transverse diameter of the rib cage (4).…”
Section: Introductionmentioning
confidence: 99%
“…The action of the RA produces a caudal displacement of the sternum, and a decrease in the anteroposterior diameter of the rib cage (4). Contraction of the EO causes a caudal displacement and a decrease in the transverse diameter of the rib cage (4). The activities of the TrA and IO are related to changes in intraabdominal pressure (5).…”
Section: Introductionmentioning
confidence: 99%